Ensuring Transport Safety of Bridges - Gulomovich, Ganiev Inomjon; Gulomov, Doston; Ravshanova, Dildora (European Journal of Life Safety and Stability (2660-9630), 2022)
The article presents the results of the research activities of the authors to ensure the transport safety of operated bridges.